Microbial gut diversity in four grasshopper species and its correlation with cellulose digestibility - Ling, Yao; Li, Wen-Jing; Li, Fei-Fei; Xue, Xiao-Bao; Gao, Yuan-Yi; Wang, Li; Liang, Ke; Li, Xin-Jiang (Frontiers in Microbiology, 2022)
Grasshoppers are common pests, and their intestinal microbes have coevolved with them. These microorganisms have varied community structures, and they participate in the nutritional absorption and metabolism of grasshoppers. Here, we describe the gut microbiota diversity of four species of grasshoppers, Oxya chinensis, Pararcyptera microptera meridionalis, Gastrimargus marmoratus, and Calliptamus abbreviatus. We constructed a 16S rDNA gene library and analyzed the digestibility of cellulose and hemicellulose in grasshoppers using moss black phenol and anthrone colorimetry. The grasshopper with the highest microbial diversity in the gut among the four species was Oxya chinensis, and there were no significant differences in gut microbial diversity between the two geographic collections of Oxya chinensis. The most dominant phyla of the four grasshopper gut microorganisms were Proteobacteria, Bacteroidetes, and Firmicutes, and the most dominant genus was Enterobacter. The gut microbiota features of the four grasshoppers were correlated with their cellulose and hemicellulose digestibility. There was a significant positive correlation with cellulose digestibility for Pantoea. A significant negative correlation was found with cellulose digestibility for Acinetobacter, Enterococcus, Citrobacter, Serratia. A significant negative correlation was found with hemicellulose digestibility for Pantoea. This study contributes to the understanding of the structural composition of different species of grasshopper gut microbiota, which may be useful for developing grasshopper digestive tracts as bioreactors for cellulose decomposition, improving the decomposition and utilization of agricultural straw, producing clean biomass energy, and processing biologically derived products.